Best practices: strengthening policy research capacity around the world - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
This is a review of the options for capacity strengthening for policy research, an overview of IFPRI’s work in this area, and a summary of the best practices in capacity strengthening, as shown by experience.